2014
DOI: 10.4161/23723548.2014.964033
|View full text |Cite
|
Sign up to set email alerts
|

Reactive oxygen species: The good, the bad, and the enigma

Abstract: Work carried out primarily in the laboratory of Fabrizio d’Adda di Fagagna unveils the mitogenic properties of Ras-induced reactive oxygen species (ROS) and their relationship with the DNA damage response. Combined data from studies of cultured cells, zebrafish models, and clinical material consistently support a role of the RAS-RAC1-NOX4 axis in ROS induction, hyperproliferation, and senescence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 9 publications
0
18
0
Order By: Relevance
“…Similarly, we have previously shown that NOX1 activation in xeroderma pigmentosum type C (XPC)-deficient cells triggers neoplastic transformation of keratinocytes and premature skin aging (Hosseini et al, 2015b;Rezvani et al, 2011aRezvani et al, , 2011b. Moreover, up-regulation of NOXs in several cancers (Liu-Smith et al, 2014;Roy et al, 2015), as well as the capability of NOXs to modulate the proliferative capacity and replicative senescence in various cells (Block and Gorin, 2012;Ogrunc, 2014), support this notion. In this study, we report that NOX1 is up-regulated after acute and chronic UVB irradiation and that inhibition of its activation modulates the DDR network.…”
Section: Introductionmentioning
confidence: 64%
See 3 more Smart Citations
“…Similarly, we have previously shown that NOX1 activation in xeroderma pigmentosum type C (XPC)-deficient cells triggers neoplastic transformation of keratinocytes and premature skin aging (Hosseini et al, 2015b;Rezvani et al, 2011aRezvani et al, , 2011b. Moreover, up-regulation of NOXs in several cancers (Liu-Smith et al, 2014;Roy et al, 2015), as well as the capability of NOXs to modulate the proliferative capacity and replicative senescence in various cells (Block and Gorin, 2012;Ogrunc, 2014), support this notion. In this study, we report that NOX1 is up-regulated after acute and chronic UVB irradiation and that inhibition of its activation modulates the DDR network.…”
Section: Introductionmentioning
confidence: 64%
“…DDR inactivation allows the oncogeneinduced senescence to be bypassed and thus induces the proliferation of oncogene-expressing cells and their transformation (Bartkova et al, 2006;Di Micco et al, 2006). In support of this notion, inhibition of NOX-induced ROS production was reported to be an effective strategy to reduce hyperproliferation and to prevent DDR activation and oncogene-induced senescence in oncogenic Ras-expressing cells (Kodama et al, 2013;Ogrunc, 2014). On the contrary, NOX1 overexpression was shown to enhance the tumorigenic conversion of NIH3T3 cells (Suh et al, 1999) and to increase neoplastic progression of immortalized human keratinocytes (Chamulitrat, 2010).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Approximately 90% of intracellular ROS are estimated to be produced during OXPHOS in mitochondria [57]. Proper ROS levels stimulate cell proliferation, mediate signal cascades, and initiate immune responses, but excessive ROS levels lead to cell death [58]. erefore, when ROS are induced, the cell activates antioxidant mechanisms for homeostasis [59].…”
Section: Mitochondrial Ros Generation and The Keap1-nrf2mentioning
confidence: 99%